Dinâmica espaço-temporal da ocorrência de nematoides em seringueira - Pezzoni Filho, José Carlos [UNESP] (2014)
In the last years, the rubber tree culture have expanded for Center-west and Southeast regions of Brazil, and with that, many phytosanitary problems have occurred, among them, there is the phytoparasitism of Meloidogyne exigua nematode. Its incidence in plants causes damages, which reduce the latex production and, occasionally, causes plants' death, which, consequently, damages the rubber tree development and crop profitability. The aim was to study the evolution of parasitism over time and space, studying the current population of nematodes in different clones and periods and analyzing satellite images. The study area is located in Itiquira municipality, Mato Grosso State, Brazil, in a total area of 6.646-planted ha with 22 rubber tree clones. Through visual analysis of satellite imagery, failures (defoliation and drought pointers) in canopy have been defined georreferencing points for sampling in field, based in RGB composition of Landsat 5 satellite's image of November 11, 2004. In the experimental area the nematode infestation 4 natural and then for soil and plants roots sampling collecting, it have been selected 265 points in May and 227 in November with its respective geographic coordinates. The sampling collecting have done in defoliation periods and after the rubber tree refoliation, in May and November 2013, respectively. These were in the same points, where it has verified the population variation in this period, occurring more infestation in May than November, both roots and soil analysis. The nematological analysis has done in roots and soil samples. These data have been used for interpolation (kriging) of populations for M. exigua spatial distribution mapping in 5 clones in major area, as GT 1, PB 217, PB 235, ...